TINGKAT PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PEMBANGUNAN PENYEDIAAN AIR MINUM DAN SANITASI MASYARAKAT (PAMSIMAS) DI DESA MARINDI KECAMATAN HARUAI KABUPATEN TABALONG (JAPB, 2022)
The forms of participation consist of 3 forms: Participation in the planning stage, Participation in the implementation stage and participation in the utilization stage. However, the variety and level of participation is often found in the number of individuals involved. The success of the implementation of development depends on the role of government and society, both of which must be able to work together. Without involving the community, the government will never achieve optimal development results, and vice versa without the government's role, development will not run in an orderly and directed manner. The purpose of this study was to determine the level of community participation in the implementation of the Development of Community Water Supply and Sanitation (Pamsimas) in Marindi Village, Haruai Sub-District, Tabalong Regency. The method used in this research is a descriptive approach with quantitative techniques. The data analysis used is tabulation analysis using the frequency formula put forward by Muhammad Ali (1998:184). While the data collection techniques in this study are: 1) Observation 2) Questionnaire (questionnaire) 3) Documentation. The questionnaires were distributed to 40 families from RT 03 to RT 07 so that each RT had 8 families who received questionnaires for discussion. The results of this study indicate that the Level of Community Participation in the Implementation of Community Water Supply and Sanitation Development (PAMSIMAS) in Marindi Village, Haruai Sub-District, Tabalong Regency is categorized as Medium. This can be seen from the recapitulation results with a percentage of 44.4%. Keywords: Level of Community Participation, Development.